The Knowledge, Attitude and Practices regarding HBV Infection of Married Women in the Reproductive Age Group living in different districts of Bangladesh (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 61-63 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12547